Association of ultra-processed foods with phenotypic age acceleration in US adults: a mediation analysis of body mass index in the NHANES - Kong, Weiliang; Xie, Yilian; Cen, Mengyuan; Xiong, Kunlong (Frontiers in Nutrition, 2025)
BackgroundThe rising intake of ultra-processed foods (UPFs) has been linked to adverse health outcomes, yet its impact on aging acceleration remains unclear.ObjectiveThis study aimed to examine the association between the percentage of total daily calories (%Kcal) and grams (%Gram) from UPFs and phenotypic age acceleration (PhenoAgeAccel).MethodsData from 12,079 adults in the NHANES 2005–2010 cycles were analyzed. The relationship between UPFs intake and PhenoAgeAccel was assessed using multivariable linear regression and restricted cubic splines, with adjustments for relevant covariates. The mediating role of body mass index (BMI) was also explored.ResultsA significant positive linear association was observed between UPFs intake (%Gram) and PhenoAgeAccel, with the highest quartile showing an increase of 0.60 (95% CI: 0.15, 1.05; p for trend = 0.039), but no association was found between UPFs intake (%Kcal) and PhenoAgeAccel. Mediation analysis indicated that BMI mediated 27.5% of the association between UPFs intake (%Gram) and PhenoAgeAccel. Sensitivity analyses confirmed the robustness of the results.ConclusionHigher intake of UPFs intake (%Gram) is positively associated with PhenoAgeAccel, with BMI playing a significant mediating role.